Effect of metformin therapy on muscle mass and strength in patients with and without diabetes. Meta-analysis of 15 studies - A. V. Sokolova; A. V. Klimova; D. O. Dragunov; G. P. Arutyunov (Российский кардиологический журнал, 2021)
Aim. To assess the parameters reflecting sarcopenia (body composition, muscle strength, muscle function) in order to determine the effectiveness of metformin in patients with sarcopenia.Material and methods. Systematic searches of clinical trials were carried out in MEDLINE databases through PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), ResearchGate from January 1990 to March 2019. For statistical processing, the R language with the RStudio software was used. The following packages were used: googlesheets4, tidyverse, meta, dmetar, metafor. The metaanalysis included 391 patients with both established for the first time and existing long-term type 2 diabetes (T2D), with prediabetes, impaired glucose tolerance (IGT), as well as patients without impaired glucose metabolism. In comparison groups (194 patients who received metformin and 197 patients who received placebo), the effect of metformin on lean body mass (LBM), fat mass, muscle strength and muscle function was assessed, which made it possible to indirectly evaluate the potential effect of metformin on sarcopenia.Results. The use of metformin in patients with different glucose metabolism (type 2 diabetes, IGT, prediabetes) did not lead to significant changes in body composition (on average, LBM increased by 0,9 kg (MD, 0,8815; CI (-0,11; 1,87), p=0,0818), fat mass decreased by 0,7% (MD, -0,6856; CI (-1,54; 0,17), p=0,1170), but muscle strength significantly increased by 0,5 kg (SMD, 0,5241, CI (0,2265; 0,8217), p=0,0006).Conclusion. Meta-analysis has confirmed that the use of metformin has an effect on muscle strength, which makes it possible to consider it for sarcopenia treatment. Unfortunately, a small number of studies have not allowed to analyze the effect of metformin on a number of characteristics: muscle strength, muscle function (walking speed, functional tests). At the moment, a much larger prospective study is needed to form a final opinion on the rationale of metformin therapy in patients with sarcopenia.